How The Choice of Academic Majors and Students' Future Achievements According to The Talent Path - Zulkifli Amin; Burhanuddin Burhanuddin; Teuku Fajar Shadiq; Anwar Soleh Purba (Universitas Pesantren Kh Abdul Chalim Mojokerto, 2021)
This article described college majors' choices on future learning achievement according to students' talents. The researcher believes that selecting majors according to talent will determine students' success in the future. So, to prove this assumption, we proved it through a study of several related kinds of literature from several educational and higher education journal publications. The publications in question are, for example, ERIC, Google Book, Elsevier, Sagepub, and Taylor and France, which were published ten years ago. We designed this qualitative study with a phenomenological approach. We explored as much data as possible that addresses student choice significant variables and academic achievement when students enter the study period. The analysis model that we did is through data coding, evaluation, and in-depth interpretation to conclude to answer questions on the principle of validity. Based on the findings and discussion data, we could conclude that there is an influence between the choice of majors and college achievement because achievement will be obtained if the field of study follows students' interests and talents. Without interest and talent, it is challenging to achieve porosity following expectations.